Dinamika Integrasi Teori Hukum Global dalam Evolusi Sistem Hukum Indonesia - Nur Atiqatul Futuhiyah; Rais Amin Mahmud (Sekolah Tinggi Agama Islam Az-Zain Sampang, 2024)
This article discusses the dynamics of law in Indonesia in an effort to integrate global legal theories into the national legal system. In the context of globalization, the interaction between international law and national law has become increasingly complex, influencing various aspects of societal life. This research analyzes how Indonesia faces the challenges and opportunities arising from the influence of global law, as well as the strategies implemented to adapt and integrate global legal principles without disregarding local values. Through a qualitative approach and analysis of various regulations and legal practices, the findings indicate that although there are obstacles in the integration process, there are also progressive initiatives in formulating legal policies that are responsive to global developments. This journal is expected to contribute to the understanding of the relationship between national and international law and provide recommendations for the formulation of more effective legal policies in Indonesia